Poverty in American Eyes - Lee Rainwater (Luxembourg Income Study (LIS), 1992)
This study proposes a social rather than an economic conception of poverty in the U.S., exploring the definition of poverty line from this perspective. Data from three sources is used to describe poverty rates in the U.S. in relation to changes over time, a cross national perspective, and variations in persistent poverty for race, sex and age.
Keywords: 330